Humorous actions, play, and rules : intersubjective and development perspective - Reyes-Rojas, Monica; Sánchez Ríos, Hernán; Simão, Lívia Mathias (Advances in subjectivity and development, 2024)
"This book proposes a hermeneutic, phenomenological, and sociocultural route, illuminating new methodological approaches to study humorous actions through Vygotsky's proposal, which has been little explored and worked on from the developmental psychology approach, specifically the rules management Higher psychological process. Reading this text clarifies how humor is a mechanism for development and, at the same time, it is a source of creativity and novelty that emerges from the intersubjective matrix to the Cultural Psychology of development and Semiotic cultural constructivism"--